Edukasi dan Implementasi Zakat, Infak, Sedekah, dan Wakaf Produktif Bagi Jama’ah Masjid Al-Munawwarah - Samsuri, Samsuri; , Warto, , Warto; Aurellia , Amanda; Yuliadi, Iqbal (Kusuma: Jurnal Pengabdian kepada Masyarakat, 2024)
The purpose of this education is to increase Muslims' understanding of the urgency of zakat to be able to be involved in ZISWAF. Held once a week, 60 minutes per session at the Al Munawwarah Mosque from 1-30 May 2024 with 50 participants. The lecture presented consisted of 4 modules with a lecture format with interactive discussion. As a result of this education, most of the congregation understands the urgency of ZISWAF and has the desire to play an active role in ZISWAF.